Predation: direct and indirect impacts on aquatic communities - Kerfoot, W Charles | Sih, Andrew (Estados Unidos | ESTADOS UNIDOS University Press Of New England / Washington, 1987)
Contents: Direct interactions; Components nad collective properties; Types of indirect interactions; Food web dynamics; Ecological adjustments in time and space
Sin Especificar
Keywords: Ecología acuática | Comunidades bióticas | Adaptación-Biología